Unformatted text preview: α x = − 1 2 , α y = 1 β x = √ 3 2 , β y = 0 Use the formulae for A ∗ , B ∗ etc with α for ξ and β for η , we have A ∗ = 1 · ( − 1 2 ) 2 + 1 · ( − 1 2 ) · 1 + 1 · 1 2 = 3 4 B ∗ = 0 as should be for elliptic C ∗ = A ∗ = 3 4 The rest are zero (since they were zero and the transformation is linear) 199...
View
Full
Document
This note was uploaded on 12/22/2011 for the course MAP 2302 taught by Professor Bell,d during the Fall '08 term at UNF.
 Fall '08
 BELL,D

Click to edit the document details